2013
DOI: 10.1097/aln.0b013e3182887526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naloxone on Opioid-induced Hyperalgesia and Tolerance to Remifentanil under Sevoflurane Anesthesia in Rats

Abstract: An ultra-low dose of naloxone blocked remifentanil-induced hyperalgesia but did not change opioid tolerance under inhalant anesthesia. Moreover, the MAC increase associated with hyperalgesia was also blocked by naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
1
25
1
1
Order By: Relevance
“…5 The naloxone dose was selected based on its ability to block opioid-induced hyperalgesia in rats. 6,22 Ibudilast (100 mg, TCI Europe N.V., Amsterdam, the Netherlands) was dissolved in 2% Tween and 20% phosphate-buffered saline at 5 mg/mL. Remifentanil (Ultiva) was obtained from Glaxo-Smith-Kline (Madrid, Spain), naloxone was obtained from Kern Pharma (Terrasa, Spain), and sevoflurane (Sevorane) was obtained from Abbott Laboratories (Madrid, Spain).…”
Section: Experimental Design and Drug Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The naloxone dose was selected based on its ability to block opioid-induced hyperalgesia in rats. 6,22 Ibudilast (100 mg, TCI Europe N.V., Amsterdam, the Netherlands) was dissolved in 2% Tween and 20% phosphate-buffered saline at 5 mg/mL. Remifentanil (Ultiva) was obtained from Glaxo-Smith-Kline (Madrid, Spain), naloxone was obtained from Kern Pharma (Terrasa, Spain), and sevoflurane (Sevorane) was obtained from Abbott Laboratories (Madrid, Spain).…”
Section: Experimental Design and Drug Groupsmentioning
confidence: 99%
“…[11][12][13] Interestingly, the opioid antagonist and also toll-like receptor 4 (TLR4) antagonist, naloxone, may block remifentanil-induced hyperalgesia and the associated increase in anesthetic requirements (MAC) 6 in the naive nonoperated rat. Ibudilast (AV-411) is a nonselective phosphodiesterase inhibitor and TLR4 receptor antagonist.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Our previous studies reported that remifentanil-induced hyperalgesia could be suppressed by the systemic application of lidocaine, but the underlying mechanisms remain incompletely understood. 2 Here, using a rat model, we explored the role of the primary somatosensory (S1) cortex in remifentanilinduced hyperalgesia as well as its inhibition by lidocaine.…”
mentioning
confidence: 99%
“…They are also widely used during the intraoperative period as they reduce the need for inhalational anesthetic agents. [1] However, perioperative opioid infusion is accused to result in acute opioid tolerance as the postoperative opioid requirement increases in time to provide efficient analgesia. It comes out as a decrease in drug efficacy.…”
Section: Introductionmentioning
confidence: 99%